From design policy to design quality the treatment of design in community strategies, local development frameworks and action plans - Carmona, Matthew (Thomas Telford, 2002)
This guide offers a framework for the development of a comprehensive range of design policies for a community strategy, local development frameworks and action plans. In the wake of the 2000 Urban White paper, the 2001 Planning Green Paper, the formation of the inter-professional Urban Design Alliance, and the increasingly influential work of the Commission for Architecture & the Built Environment (CABE), this is the ideal time to further the role of planning in promoting design quality.